Why has the grass been greener on one side of Hispaniola? A comparative growth analysis of the Dominican Republic and Haiti - Jaramillo, Laura (2009)
Examines whether the divergence in per capita real GDP of the two countries is the inevitable result of disparities in initial conditions. Examines also, to what extent it is the result of differences in the policies pursued in each country since 1960. Concludes that initial conditions cannot fully explain the growth divergence, but rather policy decisions have played a central role in the growth trends of the two countries.